In and Out of the Frame: The Construction of Meaning in Henry Peacham’s Minerva Britanna (1612) - Cezara Bobeica (Sillages Critiques)
From 1531, when Heinrich Steiner illustrated Alciati’s Emblemata, the emblematic genre, while it grew and developed along various lines, came to crystallize in a tripartite structure: a motto, or title, a symbolic picture, and a text. To understand the emblem, the reader had to combine the three elements, usually displayed on the same page, but also make use of exterior knowledge. The emblem is a space where various sources from different eras and, at times, geographical areas, collide and coalesce in order to convey meaning. The reader needs to step out of the tripartite frame as the emblem calls upon other texts and images that have to be reassembled. This constant dialogue between the inside and the outside is perfectly exemplified by Henry Peacham’s Minerva Britanna. The 204 emblems of his collection were all engraved by the emblematist himself who took special care to place each picture within one of the eight different frames he designed. The superposition of elements on the page is coupled with a variety of explicit and implicit sources mainly taken from the Bible, from political and moral treatises, ancient authors, bestiaries and from mythographic dictionaries. The analysis of the intertextual and intermedial relations will show the semantic process which results from embedding frames. Furthermore, the summoning of ancient authors in the margins of the text may at times result in interesting polyphonic and polysemantic effects that I shall analyse. In emblems, the meaning is never given nor fixed by the borders of the page and is often disseminated. In some cases, the intrusion of the outside may even distort the meaning, a particularly efficient strategy in political emblems as it allows subversive comments without transgressing the conventional frame of thought.